PARTICIPATION OF GERMAN-MENNONITES IN TURKESTAN EXHIBITIONS AND FAIRS (Web of Teachers: Inderscience Research, 2024)
This article reveals the cooperation of the German mennonets with the Turkestan winter farm society through the analysis of the materials of various publications of archival sources.